EXPECTATIONS OF CONSUMERS OF STORE BRAND APPARELS IN CHENNAI CITY OF INDIA - K. Sadasivan Sadasivan; Jayshree Suresh (Universitas Gunadarma, 2012)
Abstract The growth of store brands in India presents an interesting opportunity for the retailer to understand the motivations of consumers behind choice of store brands. Since, Chennai is not a saturated market, and with an expected growth of 10-12% over the next 10 years. Chennai is under-branded and under penetrated in many categories of apparels. Clearly, Chennai market has scope for more brands and all brands can co exist. Hence, among the four major metropolises in India, The data and information have been collected from 500 consumers of store brand apparels in Chennai city by adopting multi stage random sampling technique through pre-tested, structured interview schedule through direct interview method pertains to the year 2009-2010. The results shows that more than one third of consumers belong to the middle age group and nearly two third of them are married. About of half of the consumers are graduates and majority of consumers belong to middle income group. The results show that more than half of the consumers are employed in private sector and nearly two third of them visit the apparel store once in a month followed by every two months. The spouse and children are highly influencing the purchasing decision and most of them suggest the price of apparel store brands and nearly half of them purchase store brand apparels worth of Rs..2001-3000 per visit. The discriminant analysis indicates that lift/elevator, price tag, lighting and accessories discriminate best among age groups while comfortable, courtesy, convenience and quick delivery discriminate best among income groups. Hence, it is suggested that styling should be specific and sensitive to the large-size male consumers taking into account fashion ability and uniqueness. To remain competitive, apparel stores must continue low pricing and weekly sale advertisements. In addition, stores must continue to promote their store labels and brands as well as focus on small niche markets. Without a combination of low price and high quality, store brands will not succeed. Low price store brands end up eliminating price competition, which intensifies consumer price sensitivity, satisfaction and loyalty. Keywords: Store Brands, Consumers Expectations, Discriminant Analysis